Biosynthesis of silver nanoparticles using pearl millet (Pennisetum glaucum) husk to remove algae in the water and catalytic oxidation of benzyl alcohol. (20th August 2021) - Musere, Paidamoyo S.F.; Rahman, Ateeq; Uahengo, Veikko; Naimhwaka, Johannes; Daniel, Likius; Bhaskurani, Sandeep V.H.S.; Jonnalagadda, S.B.
Abstract: A novel protocol is developed for the first time for synthesis of Silver Nanoparticles (Ag-NPs). Ag-NPs were biologically synthesised using Pearl Millet ( Pennisetum glaucum ) husk. The Ag-NPs were investigated for their antimicrobial property against algae, and further Ag-NPs doped charcoal was explored for catalytic oxidation of benzyl alcohol in the presence of hydrogen peroxide selectively to benzaldehyde. The antimicrobial property of the Ag-NPs was tested by incubating freshwater algae in an Ag-NP solution, and the chlorophyll concentration measured periodically. The UV–Vis Spectroscopy analysis of Ag-NPs revealed a Surface Plasmon Resonance peak at 429 nm. Scanning and Transmission Electron Microscopy showed spherical shaped and poly-dispersed nanoparticles with an average size of 17 nm. Fourier Transform Infrared Spectroscopy affirmed the role of Pearl Millet extract as a reducing and capping agent of silver ions. Incubation of algae with Ag-NPs resulted in a 41.31% reduction in chlorophyll concentration. HPLC confirmed the oxidation of benzyl alcohol to benzaldehyde, with 90% conversion. The study concluded that biologically synthesised Ag-NPs are toxic to algae and can be used for algae control in wastewater treatment, and as Ag NPs doped on the charcoal catalyst for catalytic oxidation of benzyl alcohol to form benzaldehyde. With cleaner production concept, this protocol addresses treating the algae contaminated water with Ag-NPs. An eco-friendly, economical process is developed for Namibia/Africa, which is stressed by water shortage. Further, the efficacy of Ag-NP doped charcoal as a catalyst for selective oxidation of benzyl alcohol to benzaldehyde is established. Graphical abstract: Image 1 Highlights: This work highlights about Ag NPs synthesised from Pennisetum Glaucum rice husk by biological method. A novel method developed for synthesizing AgNPs from Pennisetum Glaucum for the first time a concept of Cleaner Production. Ag NPs for treatment of water contaminated with Algae. Antimicrobial activity of AgNPs on algae. AgNPs doped on charcoal for selective oxidation of benzyl alcohol to benzaldehyde.